A structural model of vocational pre-service teachers’ quality via Tamansiswa values, motivation, and transformational leadership: PLS-SEM approach - Rabiman, Rabiman; Mutohhari, Farid; Nurtanto, Muhammad; Handoyono, Nurcholish Arifin; Bako, Ibrahim Haruna (Jurnal Pendidikan Vokasi, 2026)
Improving the teaching quality of vocational pre-service teachers requires integrative strategies that combine cultural values, motivation, and leadership development. This study examines the direct and indirect effects of Tamansiswa teaching values and motivation on teaching quality, with transformational leadership as a mediating variable. A quantitative longitudinal ex post facto design was employed. Data were collected from 697 vocational pre-service teachers in Yogyakarta, Indonesia, using structured questionnaires measuring Tamansiswa teaching values, motivation, transformational leadership, and teaching quality through validated Likert-scale instruments. Data were analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM) to test measurement reliability, structural relationships, and mediation effects. The results indicate that motivation is the strongest predictor of teaching quality (β = 0.880), followed by transformational leadership (β = 0.238), while Tamansiswa teaching values show a smaller but significant direct effect (β = 0.088). Both Tamansiswa teaching values (β = 0.287) and motivation (β = 0.399) significantly enhance transformational leadership. Mediation analysis confirms that transformational leadership strengthens the effects of Tamansiswa teaching values and motivation on teaching quality. The structural model demonstrates good fit (SRMR = 0.056; NFI = 0.926). These findings position transformational leadership as a key mechanism through which indigenous values and motivation are translated into effective teaching practices. The study contributes to vocational teacher education by integrating culturally grounded values into a leadership-mediated model of teaching quality and recommends embedding value internalization, motivational support, and leadership development within pre-service teacher preparation programs.